Pediatric Advance Care Planning for a Patient with a Severe Motor and Intellectual Disorder through Cooperation between an Acute Care Hospital and a Residential Facility - Hiroshi Wada; Masahisa Funato; Kiyoshi Takemoto; Yoshitaka Iijima; Atsuko Kashiwagi; Natsuko Shiomi; Shigetoyo Kogaki; Tomoko Maruyama (Palliative Medicine Reports, 2022)
Background: With the rapid progress of medical technology, the number of children with medical complexities who require advanced medical care, including mechanical ventilators, has been increasing steadily in Japan. Accordingly, the issue of how to provide holistic care and support for the entire life of the children with severe motor and intellectual disabilities (SMID) who live at home has become a new challenge. Case Presentation: We present the case of a three-year-old boy with SMID due to HHV-6B-induced hemorrhagic shock encephalopathy who was cared for at home by the home visit medical team of Osaka Developmental Rehabilitation Center (ODRC; residential facilities with the department of home medical treatment and care). He developed septic shock triggered by an urinary tract infection and was admitted to Osaka General Medical Center (OGMC; acute care facility not directly affiliated with ODRC), where he deteriorated to a terminal stage. After discussing advance care planning (ACP) with his parents, along with the medical team, an ACP document with parental wishes was created through collaboration between the two facilities. The document was approved by the Ethics Committee at OGMC and the parents signed the document. Special end-of-life care planning was given by nurses at OGMC based on the best interests of the patient and the family. The patient passed away peacefully surrounded by his family in a private room of OGMC according to the ACP, despite special limitations caused by the coronavirus disease 2019 (COVID-19) pandemic. Conclusions: ACP provides a good opportunity to think about the best total care for a child with SMID, for whom it is too difficult to express his or her wishes, together with the parents, who are the legal representatives. The collaboration between two institutions with different roles brought out the best of each, and the resulting ACP was beneficial to the patient and their family.